Leveraging Technology for Infrastructure Condition and Performance Assessment - Aktan, Ahmet Emin; Moon, Franklin L.; Weidner, Jeffrey Scott (Frontiers in Built Environment, 2016)
The primary objective of this discussion is to argue that the need for innovation in civil engineering practice is becoming more critical, especially as the goals and expectations associated with infrastructure performance expand to include Livability, Sustainability, and Resilience (LSR). Current approaches to assess and characterize constructed infrastructures rely primarily on visual inspection procedures, which largely serve to guard against blatant safety problems. These efforts generally include a thorough documentation of visual appearance guided by heuristics. Unfortunately, the relationship between key limit states (e.g. structural safety, serviceability, functionality, etc.) and visual condition is nebulous and thus decision-makers are often forced to rely on conservatism at the expense of accuracy. Further, documenting visual distresses do not always lend to understanding the root causes. As a result, visual assessment procedures make organizations struggle to design proper and effective maintenance and make prudent asset management decisions. In general completely visual infrastructure evaluation may lead to incomplete diagnoses followed by ineffective prognoses, often leading to highly consequential disruptions impacting LSR. To illustrate this argument further the paper draws upon the authors’ experiences evaluating bridges over the last several decades. More specifically, this paper aims to present an overview of the current highway bridge engineering and management practices in the US and to postulate how technologies may be incorporated to achieve LSR goals. Wherever possible, the authors have tried to present this discussion in sufficiently general terms as many aspects of it may equally apply to other infrastructure nodes and sectors as well.